Experimental Assessment of Physician Modified Proximal Scalloped Stent Graft to Extend Proximal Landing Zone in the Aortic Arch. (August 2017) - Faure, E.M.; Khantalin, I.; Peyron, P.A.; Canaud, L.; Marty-Ané, C.; Alric, P.
Abstract : Objective/Background: The aim of the study was to assess a model of physician modified scalloped stent graft (PMSG) on currently available thoracic aortic devices to extend the proximal landing zone in either zone 2, 1 or 0 of the aortic arch while preserving flow in the supra-aortic vessels on human cadaveric aorta. Methods: Fresh human aortas were harvested at autopsy from adult subjects. A proximal scallop was made on the stent grafts based on direct measurements on the aortas to extend the proximal landing zone in zone 0 ( n = 5), zone 1 ( n = 5), and zone 2 ( n = 5). A previously described benchtop closed system pulsatile flow model was used to mimic flow and pressure conditions in the aorta to deploy the stent graft as close to physiological conditions as possible. Deployment accuracy of the scallop opposite the aortic arch branch ostia was assessed by completion angiography and post-procedural analysis of the aortas. Results: Fifteen proximal scalloped stent grafts were deployed in the aortic arch of 15 human cadaveric aortas under fluoroscopy. The expected proximal landing zone was achieved in all cases (zone 2 = 5; zone 1 = 5; zone 0 = 5). Post-procedural angiography and direct visual analysis showed supra-aortic vessel patency and deployment of the scallop opposite the aortic arch branch ostia in all cases. Conclusion: PMSG to extend the proximal landing zone in zone 2, 1, or 0 in order to treat urgent diseases of the proximal descending aorta or the inner circumference of the aortic arch by a totally endovascular approach while preserving flow in the supra-aortic trunks is experimentally feasible.